A Prototype Dual-Feedback CPM Device: Precision ROM and EMG Integration for Knee Rehabilitation - Rakthum, Ploypailin; Maneetham, Dechrit; Aung, Myo Min; Rabgyal, Tenzin (Engineering, Technology & Applied Science Research, 2026)
Existing knee Continuous Passive Motion (CPM) devices lack physiological feedback, and therefore cannot verify whether muscles are actively engaged during rehabilitation. This study presents a dual-feedback knee CPM device that integrates precise Range of Motion (ROM) control with real-time muscle activity monitoring. Encoder feedback enables closed-loop ROM control from 22° to 90°, with adjustable movement speeds from 0.64°/s to 4.39°/s, achieving high positional accuracy (Root Mean Square Error (RMSE) 0.0303–0.5802°) across repeated cycles. Surface Electromyography (EMG) measurements of the Rectus Femoris (RF) capture muscle activity, showing low activation during extension (EMG values of 50–150) and increased activation during flexion (EMG values of 250–350). The synchronized ROM and EMG signals confirm a temporal correlation between joint motion and muscle response, demonstrating that the system can quantify both positioning accuracy and muscle activation behavior during CPM-assisted movement. The integration of ROM precision and EMG monitoring forms a novel dual-feedback architecture for knee CPM rehabilitation, enabling objective and data-driven evaluation rather than subjective observation.